(untitled) (The Peerian Journal, 2023)
In this article, the theory of the formation of a pedagogical person who fully meets the requirements of the reforms implemented in society today, is resistant to competition in the field of production, can adapt to sudden changes, and also works effectively at the level of the requirements for the qualifications of specialists in the labor market the basics are covered.